Assessment of structural and functional changes in recipient's transplanted heart in the long-term postoperative period - M. Sh. Khubutiya; Kh. G. Alidzhanova; A. V. Dyatlov; A. A. Ivannikov; S. Yu. Shemakin; D. A. Kosolapov (Трансплантология (Москва))
Introduction. Heart transplantation is an effective way of treating patients with end-stage heart failure. Echocardiography allows for the assessment of the transplanted heart functions at all stages of follow-up. The clinical implementation of myocardial deformation imaging by the speckle tracking echocardiography has made it possible to detect subtle changes in myocardial contractility.Objective. To study the structural and functional state of myocardium in recipients in the long term after orthotopic heart transplantation.Material and methods. The study included 13 orthotopic heart transplant recipients (11 men and 2 women) at a mean age of 54.1±9.1 years who underwent orthotopic heart transplantation at the N.V. Sklifosovsky Research Institute for Emergency Medicine. The mean follow-up period after orthotopic heart transplantation was 6±0.7 years. All patients underwent transthoracic echocardiography according to the standard protocol, including determination of left ventricular myocardial deformation.Results. The median volume of the left atrium was 60 (53;76) ml, the left ventricular end-diastolic volume was 76 (70;90) ml, and the end-systolic volume was 30 (24;36) ml. The median ejection fraction of the left ventricle in the studied sample was 64 (57;66)%. The median interventricular septum thickness was 12 (11;13) mm, the left ventricular posterior wall thickness was 9 (8;10) mm. At the same time, the left ventricular myocardial mass and the left ventricular myocardial mass index were within the normal range and amounted to 140 (121;155) g and 65 (58;76) g/m2, respectively. The right heart chambers were not dilated, as the volume of the right atrium was 41 (40;56) ml, and the right ventricular enddiastolic dimension was 32 (30;33) mm. The right ventricular systolic function was unimpaired: the tricuspid annular plane systolic excursion was 18 (17;19) mm, and the right ventricular fractional area change was 46 (37.5;47.0)%. The calculated systolic pulmonary artery pressure was within the normal range 24 (21;28) mm Hg. The measurements of left ventricle global longitudinal and circumferential strains were -19.6 (-18.6;-21.2)% and -30.9 (-28.8;-32.0) %, respectively. Patients in the study sample showed a decrease in the left ventricular global function index to 25 (24.2;29.6)%. The diastolic dysfunction of a restrictive type was present in 10 patients (76.9%).Conclusions. In the long-term period after heart transplantation, the recipients were found to have a low left ventricular ejection fraction and a diastolic dysfunction of the restrictive type. Considering the normal values of left ventricular myocardial strains, we can assume that after 6 years post-orthotopic heart transplantation, the recipients have restored the heart adaptive functions, and a favorable outcome has been achieved. However, long-term monitoring is required.